Liver Transplantation in the Time of a Pandemic: A Widening of the Racial and Socioeconomic Health Care Gap During COVID-19. Issue 3 (September 2021) - MacConmara, Malcolm; Wang, Benjamin; Patel, Madhukar S.; Hwang, Christine S.; DeGregorio, Lucia; Shah, Jigesh; Hanish, Steven I.; Desai, Dev; Lynch, Raymond; Tanriover, Bekir; Zeh, Herbert; Vagefi, Parsia A.
Abstract : Objective: During the initial wave of the COVID-19 pandemic, organ transplantation was classified a CMS Tier 3b procedure which should not be postponed. The differential impact of the pandemic on access to liver transplantation was assessed. Summary Background Data: Disparities in organ access and transplant outcomes among vulnerable populations have served as obstacles in liver transplantation. Methods: Using UNOS STARfile data, adult waitlisted candidates were identified from March 1, 2020 to November 30, 2020 (n = 21, 702 pandemic) and March 1, 2019 to November 30, 2019 (n = 22, 797 pre-pandemic), and further categorized and analyzed by time periods: March to May (Period 1), June to August (Period 2), and September to November (Period 3). Comparisons between pandemic and pre-pandemic groups included: Minority status, demographics, diagnosis, MELD, insurance type, and transplant center characteristics. Liver transplant centers (n = 113) were divided into tertiles by volume (small, medium, large) for further analyses. Multivariable logistic regression was fitted to assess odds of transplant. Competing risk regression was used to predict probability of removal from the waitlist due to transplantation or death and sickness. Additional temporal analyses were performed to assess changes in outcomes over the course of the pandemic. Results: During Period 1 of the pandemic, Minorities showed greater reduction in both listing (−14% vs −12% Whites), and transplant (−15% vs −7% Whites), despite a higher median MELD at transplant (23 vs 20 Whites, P < 0.001). Of candidates with public insurance, Minorities demonstrated an 18.5% decrease in transplants during Period 1 (vs −8% Whites). Although large programs increased transplants during Period 1, accounting for 61.5% of liver transplants versus 53.4% pre-pandemic ( P < 0.001), Minorities constituted significantly fewer transplants at these programs during this time period (27.7% pandemic vs 31.7% pre-pandemic, P = 0.04). Although improvements in disparities in candidate listings, removals, and transplants were observed during Periods 2 and 3, the adjusted odds ratio of transplant for Minorities was 0.89 (95% CI 0.83–0.96, P = 0.001) over the entire pandemic period. Conclusions: COVID-19's effect on access to liver transplantation has been ubiquitous. However, Minorities, especially those with public insurance, have been disproportionately affected. Importantly, despite the uncertainty and challenges, our systems have remarkable resiliency, as demonstrated by the temporal improvements observed during Periods 2 and 3. As the pandemic persists, and the aftermath ensues, health care systems must consciously strive to identify and equitably serve vulnerable populations.